Failure analysis of cyclic damage to a railway rail – A case study - Fedorko, Gabriel; Molnár, Vieroslav; Blaho, Peter; Gašparík, Jozef; Zitrický, Vladislav (Engineering failure analysis, 2020)
•• Non-traditional case of cyclic damage to rails of considerable length (21,725 m).•• Analysis of the cause of damage and the analysis of the damage removal method.•• The analysis 5725 defects-an unconventional rarity in terms of the number of defects.•• Horizontal cracks can branch downwards and cause the rail to break. Various damage to the railway rail has a significant impact on the operation safety and life of the railway infrastructure. The paper focuses on failure analysis of rare cyclic damage to the surface of a railway rail loaded with normal operation. Straining of the rail at the point of contact with a railway wheel, due to vertical forces, causes permanent deformation of the rail surface. The research is focused on a non-traditional case of cyclic damage to rails on a continuous track section of considerable length (21,725 m), on the analysis of the cause of damage and on the analysis of effectiveness of the damage removal method. The methodology used consists of a visual field study using conventional measurement methods, supported by a non-destructive on-site inspection to identify the severity of deficiencies in railway safety; and to measure the effectiveness of operator maintenance policies that need to be improved to identify and correct infrastructure extensions. In total, the section was analyzed that showed 5725 defects, which is an unconventional rarity in terms of the number of defects and has not been scientifically investigated yet.